A generalised CIR process with externally-exciting and self-exciting jumps and its applications in insurance and finance - Angelos Dassios; Jiwook Jang; Hongbiao Zhao (Risks, 2019)
In this paper, we study a generalised CIR process with externally-exciting and self-exciting jumps, and focus on the distributional properties and applications of this process and its aggregated process. The aim of the paper is to introduce a more general process that includes many models in the literature with self-exciting and external-exciting jumps. The first and second moments of this jump-diffusion process are used to calculate the insurance premium based on mean-variance principle. The Laplace transform of aggregated process is derived, and this leads to an application for pricing default-free bonds which could capture the impacts of both exogenous and endogenous shocks. Illustrative numerical examples and comparisons with other models are also provided.
Keywords: 330; aggregate claims; CIR process; contagion risk; default-free bond pricing; hawkes process; insurance premium; self-exciting process